The Personalization of Clopidogrel Antiplatelet Therapy in Coronary Artery Disease Patients using Pharmacometabonomics, Pharmacogenetics and Platelets Function Testing - Mostafa, Arwa Mohamed Amin (2016)
Clopidogrel is a substantial antiplatelet drug. Some patients on clopidogrel treatment suffer from high on treatment suffer from high on treatment platelets reactivity (HTPR) which may lead to poor outcome.